Generalized - diffusive theory of solid mixtures. III. Anisotropy and wave propagation in compozite material - Chanh, Truong Minh (Vietnam Journal of Mechanics, 1984)
In this paper the linear elastic constitutive equations for anisotropic compozite mate rial are obtained. The wave propagation in this material is discussed.